2019
DOI: 10.21203/rs.2.12440/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Regulatory Networks for Salt-Alkali Stress in Gossypium hirsutum With Differing Morphological Characteristics

Abstract: Background Cotton grows in altering environments that are often unfavorable or stressful for its growth and development. Consequently, the plant must cope with abiotic stresses such as soil salinity, drought, and excessive temperatures. Alkali-salt stress response remains a cumbersome biological process and is regulated via a multifaceted transcriptional regulatory network in cotton Results To discover the molecular mechanisms of alkali-salt stress response in cotton, a comprehensive transcriptome analysis was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, there is no information on transcriptome analysis in relation to N and other nutrients in cotton. Some reports showed that the quantity of DEGs under salt stress varied from 3800 to 22,000 in cotton [ 51 , 52 ]. Han et al identified 4627 DEGs in cotton under cadmium (Cd) toxicity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no information on transcriptome analysis in relation to N and other nutrients in cotton. Some reports showed that the quantity of DEGs under salt stress varied from 3800 to 22,000 in cotton [ 51 , 52 ]. Han et al identified 4627 DEGs in cotton under cadmium (Cd) toxicity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%